Best Answer

It is: -73--27 = -46 because a double minus becomes a plus and --27 is the same as +27

Q: What is -73 - -27?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

The difference is 46

46

The number one rule is "what you do to one side, you must do to the other". So to demonstrate in detail: e - (-73) = -27 e - (-73) + 73 = -27 + 73 e = 46

27/73 is in its simplest form.

They are all perfect cubes. 8 = 23, 27 = 33, 343 = 73, 64 = 43 and 125 = 53.

Related questions

The difference is 46

73 + 27 = 100

73/n = 27 Therefore, 73/27 = n Therefore, n = 2.703 recurring (that is, 2.703703703...)

46

The number one rule is "what you do to one side, you must do to the other". So to demonstrate in detail: e - (-73) = -27 e - (-73) + 73 = -27 + 73 e = 46

27+73=100 You need to add 73 to 27 to get 100.

27/73 is in its simplest form.

100 - 27 = 73 (the percentage of 300 that is 27 percent short of 300) 300x (27/100) = 300x .73 = 219

73 is the prime number.

0.369863

Jeopardy - 1984 27-73 was released on: USA: 22 December 2010

109-36=73 73+27=100 Ans:100 ?